Internalization of near-infrared fluorescent dyes within isolated macrophage populations - Reese, C. T.; Ntam, C.; Martin, T.V.; Carrington, S.; Leotaub, J.; Cox, L.; Williams, R. J.; Hill, D. A. (Cellular and Molecular Biology, 2007)
The development and application of microsensor technology has enhanced the ability of scientists to further understand various biological activities, such as changes in the intracellular environment after injury or toxic exposure. NIR microsensor technology may be useful in detecting the cellular injuries or adverse changes during the early onset period, allowing for the administration of therapies to initiate recovery. The development and use of Infrared (IR) and near infrared (NIR) dyes as biological micro-sensors due to their advanced spectral characteristics may be helpful. Three of the more useful NIR dye characteristics include the ability to minimize background interference by extraneous biological matrices, the ability to exhibit optimal molar absorptivity and quantum yields, and the ability to maintain normal cellular activity. Thus, the current study was designed to investigate the ability of selected NIR micro-sensor dyes to undergo cellular internalization, demonstrate intracellular NIR fluorescent signaling, and maintain normal cellular activity. The results demonstrate that the selected NIR micro-sensor dyes undergo cellular internalization. The presence of the dyes within the cells did not affect cell viability. In addition, these dyes demonstrate changes in absorbance and fluorescence after the immune cells were challenged with a stimulant. Moreover, critical cellular functions, such as tumor necrosis factor release and superoxide production were not compromised by the internalization of the fluorescent dyes. These data suggest that selected NIR micro-sensor dyes can undergo intracellular internalization within isolated macrophages without adversely affecting various parameters of normal cellular activity.